The Effect of site of tympanic membrane perforation on hearing - Farouk Al- Omari, Alyaa (Tikrit Journal of Pharmaceutical Sciences, 2023)
Tympanic membrane(TM) perforation is one of the most common causes of hearing impairment. Apart from conduction of sound waves across the middle ear, the tympanic membrane, also sub-serves a protective function to the middle ear cleft and round window niche. The aim of the study is to determine the effect of the site of the tympanic membrane perforation on hearing. Seventy-eight patients with perforated tympanic membranes were included in the study.They all have TM perforation due to recurrent or chronic otitis media. Patients with traumatic TM perforation were excluded from the study. There were 47 males (46.5%) and 54 females (53.5%). Twenty patients had left ear perforation, 35 patients had right ear perforation, and 23 patients had bilateral perforations. Each ear was taken as a case, so the total number of the perforated ear drums was 101. The age ranged from 13- 56 with the mean of age was (31.64 ± 13.249) years. The TM perforation was examined and photo image was taken with the aid of the endoscope. Controls were 55 patients with a mean age 30.73 ±12.09 (range 14-53) years. Male controls were 34 (61.8%), and 21 female controls (38.2%). There is a positive correlation between site of TM perforation and hearing level, air bone gap, low frequency hearing level and high frequency hearing level. As a conclusion, there is a positive relationship between the site of TM perforation and hearing level being more in the posterior-superior and inferior parts.